2022
DOI: 10.3390/ijms232213760
|View full text |Cite
|
Sign up to set email alerts
|

iPLA2β-Null Mice Show HCC Protection by an Induction of Cell-Cycle Arrest after Diethylnitrosamine Treatment

Abstract: Group VIA phospholipase A2 (iPLA2β) play diverse biological functions in epithelial cells and macrophages. Global deletion in iPLA2β-null (KO) mice leads to protection against hepatic steatosis in non-alcoholic fatty liver disease, in part, due to the replenishment of the loss of hepatocellular phospholipids. As the loss of phospholipids also occurs in hepatocellular carcinoma (HCC), we hypothesized that global deletion in KO mice may lead to protection against HCC. Here, HCC induced by diethylnitrosamine (DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Many efforts have been devoted to unraveling the pathological mechanisms underlining the progression of chronic liver diseases to HCC, with the final aim being to find druggable targets to prevent or cure HCC. In this regard, the study of Andrade et al suggests that the inhibition of the group VIA phospholipase A2 (iPLA2β), a protein involved in the regulation of epithelial cells and macrophage functions, could prevent HCC by inducing cell-cycle arrest [6]. They demonstrated that iPLA2β KO mice have an improved resistance to diethylnitrosamine (DEN)-induced HCC that is likely to reside in the suppression of the hepatic expression of cyclin D2 (CCND2) and B-cell lymphoma 2 (BCL2), which are involved in cell-cycle regulation, and of IL6, IL10, and VCAM-1, which are involved in inflammatory processes.…”
mentioning
confidence: 99%
“…Many efforts have been devoted to unraveling the pathological mechanisms underlining the progression of chronic liver diseases to HCC, with the final aim being to find druggable targets to prevent or cure HCC. In this regard, the study of Andrade et al suggests that the inhibition of the group VIA phospholipase A2 (iPLA2β), a protein involved in the regulation of epithelial cells and macrophage functions, could prevent HCC by inducing cell-cycle arrest [6]. They demonstrated that iPLA2β KO mice have an improved resistance to diethylnitrosamine (DEN)-induced HCC that is likely to reside in the suppression of the hepatic expression of cyclin D2 (CCND2) and B-cell lymphoma 2 (BCL2), which are involved in cell-cycle regulation, and of IL6, IL10, and VCAM-1, which are involved in inflammatory processes.…”
mentioning
confidence: 99%